Representation Minangkabau Culture in Syair Sidi Djamadi: Study of Literary Anthropology - Yosi Wulandari; Wachid Eko Purwanto; Indah Arohmawati; Riyadin Nawangsari (HISKI, 2021)
Abstract Poetry as one of the ancient Indonesian literary heritage is a discourse that holds noble teachings and culture that do not fade with the times. Discussing things related to the culture of the community, the anthropological approach is used. This study aims to describe the representation of Minangkabau culture from Syair Sidi Djamadi. The method used is content analysis method. The data of this research are aspects of religiosity as a form of cultural representation in Syair Sidi Djamadi. Syair Sidi Djamadi has 761 verses. Each stanza consists of four lines. The total number of the verses is 3044 lines. Syair Sidi Djamadi in general contains about faith, piety and piety. The data were collected by transliteration, data inventory, then analysis and interpretation were carried out, and the final step was the conclusion. The results of this study indicate that the traditional Minangkabau representation is religiosity in Sidi Djamadi's poetry, the teachings of carrying out shahada, prayer, haj, zakat, fasting, studying, learning the Koran. The dimensions of religiosity are presented as teachings that have a collective view of the Minangkabau community and are applied together as community culture. AbstrakSyair sebagai salah satu warisan sastra Indonesia kuno merupakan wacana yang menyimpan ajaran dan budaya luhur yang tidak luntur seiring perkembangan zaman. Membahas hal-hal yang berkaitan dengan budaya masyarakat, digunakan pendekatan antropologi sastra. Penelitian ini bertujuan untuk mendeskripsikan representasi budaya Minangkabau dari Syair Sidi Djamadi. Metode yang digunakan adalah metode analisis isi. Data penelitian ini berupa aspek religiusitas sebagai wujud representasi budaya dalam Syair Sidi Djamadi. Syair Sidi Djamadi memiliki 761 sajak. Setiap bait terdiri dari empat baris. Jumlah ayat adalah 3044 baris. Syair Sidi Djamadi secara umum berisi tentang keimanan, takwa dan takwa. Pengumpulan data dilakukan dengan transliterasi, inventarisasi data, kemudian dilakukan analisis dan interpretasi, dan langkah terakhir adalah penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa representasi adat Minangkabau adalah religiusitas dalam puisi Sidi Djamadi, ajaran melaksanakan syahadat, salat, haji, zakat, puasa, belajar, belajar mengaji. Dimensi religiusitas dihadirkan sebagai ajaran yang memiliki pandangan kolektif masyarakat Minangkabau dan diaplikasikan bersama sebagai budaya masyarakat.